(untitled) (Research, Society and Development, 2019)
The Innovation Pole develops actions aimed at meeting the demands of the production chains for Research, Development and Innovation (R, D & I) activities. Within its structure, has a coordination of Human Resources Training that is responsible for monitoring actions focused on the training process of students involved in projects, in order to complement their qualification in their training path and professional practices. This monitoring has within its main scope, the formalization of the entry of students in applied research projects, as well as their permanence and performance in activities, qualification, training and evaluation. Thus, the present study aims to form indicators through the quantity of students from the Federal Institute of Ceará inserted in research projects developed at the Fortaleza Innovation Pole, their origin and degree courses, as well as to understand how students are accredited, selected, trained and evaluated. The results indicate more than three hundred students in applied research projects, distributed in courses from the technical level to the doctorate. They also indicate criteria for accreditation; participation in courses, lectures and workshops to increase the selection process; assessment and self-assessment processes and use in the PBL Problem Based Learning (PBL) methodology. The results also indicate the use of a student accreditation notice, as well as instruments for their selection and evaluation.